Putative Iron-Sulfur Proteins Are Required for Hydrogen Consumption and Enhance Survival of Mycobacteria - Islam, Zahra F.; Cordero, Paul R. F.; Greening, Chris (Frontiers in Microbiology, 2019)
Aerobic soil bacteria persist by scavenging molecular hydrogen (H2) from the atmosphere. This key process is the primary sink in the biogeochemical hydrogen cycle and supports the productivity of oligotrophic ecosystems. In Mycobacterium smegmatis, atmospheric H2 oxidation is catalyzed by two phylogenetically distinct [NiFe]-hydrogenases, Huc (group 2a) and Hhy (group 1h). However, it is currently unresolved how these enzymes transfer electrons derived from H2 oxidation into the aerobic respiratory chain. In this work, we used genetic approaches to confirm that two putative iron-sulfur cluster proteins encoded on the hydrogenase structural operons, HucE and HhyE, are required for H2 consumption in M. smegmatis. Sequence analysis show that these proteins, while homologous, fall into distinct phylogenetic clades and have distinct metal-binding motifs. H2 oxidation was reduced when the genes encoding these proteins were deleted individually and was eliminated when they were deleted in combination. In turn, the growth yield and long-term survival of these deletion strains was modestly but significantly reduced compared to the parent strain. In both biochemical and phenotypic assays, the mutant strains lacking the putative iron-sulfur proteins phenocopied those of hydrogenase structural subunit mutants. We hypothesize that these proteins mediate electron transfer between the catalytic subunits of the hydrogenases and the menaquinone pool of the M. smegmatis respiratory chain; however, other roles (e.g. in maturation) are also plausible and further work is required to resolve their role. The conserved nature of these proteins within most Hhy- or Huc-encoding organisms suggests that these proteins are important determinants of atmospheric H2 oxidation.